Problematic Land Buying and Selling Transactions - Uktolseja, Novyta; Dyastuti, Risqi Mumpuni; Berlianty, Teng; Demmatacco, Triska (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Land ownership has become a primary need, but in the process of land ownership there are still problems. Basically, the acquisition of land rights according to the Decree of the Minister of Agrarian Affairs Number 21 of Article 1 Point 1, the acquisition of land is carried out by transferring land rights or through the delivery of release of land rights followed by granting rights. But this activity is not carried out in its entirety so that it will cause problems in granting rights to the community. Purposes of the Research: This research was conducted in Sanahu Village, Elpaputih District, West Seram Regency. This village prioritizes and gives importance to matters relating to customary land. However, based on the dinamics of the community, transactions carried out by the community should be carried out in accordance with the provisions of the legislation governing land registration in order to obtain legal certainty in the transactions carried out and aim for orderly administration in land sector. Methods of the Research: This research method is empirical juridical research that uses primary and secondary data. The legal materials used are primary legal materials, secondary legal materials with questionnaire and interview methods, data collection techniques with literature studies and field studies. Data processing and analysis techniques use descriptive analytical data analysis by identifying, classifying, then analyzing and describing according to the hierarchy. Results of the Research: Based on have not carried out the first land the results of the interviews, it is known that some people in Sanahu village do not know about the sale and purchase practices that should be taken in order to obtain legal certainty from the sale and purchase transactions carried out. This should be done based on the provisions of Article 19 paragraph 2 of the UUPA, Article 37 of PP 24 of 1997 concerning land registration. As a result, in the event of problems related to previous land transactions, the community had to resolve themselves in a family manner, either without or with assistance from local officials. As a result, the people of Sanahu village have not carried out the initial registration and maintenance of land registration data properly. Because land administration is not orderly, if there are land issues in transactions carried out either by transferring rights or encumbering rights, there will be problems in the future and limit land owners in carriying out legal actions.